La constitucionalización del ordenamiento jurídico peruano: avances y obstáculos del proceso - Alvites, Elena (2018)
This presentation is focused on advances and obstacles in the process of the constitutionalization of the Peruvian legal system, as it pertains to private law, labour law, and consumer protection, issues that have primarily been addressed by the Constitutional Court. The purpose of this exercise is to identify some of the strengths of this process, in broad strokes, mostly with regard to the protection of fundamental rights and their enforcement in relationships between private individuals. It also seeks to identify and reflect on —through two cases, one involving the protection of the right to collective bargaining, and the other involving the right to freedom of thought— the limits of constitutionalization, as a process and a result, in political relationships and decision-making.